The Strategies of Tofu and Fermented Soybean Cake Cooperation in Facing China-Asean Free Trade - Rusdarti, Rusdarti (Universitas Muhammdaiyah Surakarta, 2015)
This research was aimed to identify the internal and external factor for encountering free trade China-Asean and to find some strategic model alternative that can be applied by Primkopti Semarang to develop their business. The analysis methods used were descriptive analysis method and SWOT analysis. The result of this research showed that internal factors for cooperationâs strength for encountering free trade including soybean distributor in form of cooperation in Semarang and experienced manager to carry out the business. The weakness one was the research and development of cooperation hasnât been optimal and the management of information system hasnât worked well. External factors for opportunity one including the soybean buyer or main customer was cooperation members having dual identity, as for the threat including no resistance for new competitor, increasing soybean import, soybean importer has strong bargain position. Compatible strategy for cooperation implementation in encountering free trade China-Asean was market penetration strategy and product development.